Razlike v asertivnem vedenju med študentkami zdravstvene nege in študentkami drugih fakultet - Ličen, Sabina (Obzornik zdravstvene nege, 2013)
Introduction: The aim of the study was to determine whether the nursing students are equally assertive as students of other faculties of the University of Primorska and the European Faculty of Law in Nova Gorica and whether assertiveness among students increases with age. Nursing has been considered to be a typical female profession where nurses function as nurturers, comforters and care providers. The assertive behaviour among nurses was accordingly considered less pronounced than in other professionals with similar educational level. Methods: The research was based on a descriptive and non-experimental research method. A questionnaire used as a research instrument included the Rathus Assertiveness Schedule. The purposive sampling was used in this qualitative research. The access to the online questionnaire was provided through URL address which was sent to the students'common e-mail addresses at some faculties of the University of Primorska and the European Faculty of Law in Nova Gorica. The questionnaires were completed and returned by 218 female students. The survey was conducted in May and June of 2010. The data collected were analysed using the descriptive statistics and the One-Way ANOVA. Results: According to the results obtained, the nursing students do not manifest statistically significant lower assertiveness levels as compared to the students of other faculties included in the study (F = 0.37, p = 0.83). It has also been established that older students are not statistically significantly more assertive in comparison to younger female students (F = 1.52, p =0.22). Discussion and conclusion: Assertive behaviour is a core element of interpersonal relationships and an important communication skill. Learning new communication skills and behaviours in professional situations, however, is not an easy task and takes a considerable time. To function as effective and safe practitioners, nurses should be encouraged to develop appropriate assertive behavioural patterns. The education in assertiveness should be integrated in their professional preparation which necessitates also adequately qualified teachers and mentors.
Keywords: asertivnost; assertiveness; nursing care; student; students; študenti; zdravstvena nega